The grinch mountain was the answer
Answer:
(x - 2)(x + 1)(2x -1)
Step-by-step explanation:
We use synthetic division as a tool for factoring the given expression. The coefficients of the terms given are {2, -3, -3, 2}. If x - 2 is a factor of this expression, then 2 is a root. We perform synthetic division as follows:
2 / 2 -3 -3 2
4 2 -2
-------------------------------
2 1 -1 0
Next, we determine whether or not (2x - 1)(x + 1) represents the remaining factor(s). Using -1 as divisor, we get:
-1 / 2 1 -1
-2 1
---------------------
2 -1 0
Since the remainder is zero, x + 1 must be a factor and (2x - 1) the third factor. Answer D is correct.
Answer:
B and E
Step-by-step explanation:
A. -7 ÷ (-4) = -7/-4 = 7/4 = 1.75
B. -(3 ÷ 2) = -(1.5) = -1.5
C. -8/5 * (-5/8) = (8/5) * (5/8) = 1
D. -5/-3 = 5/3 ≈ 1.667
E. -9 ÷ 6 = -9/6 = -1.5
Answer:
The matrix would be:
-1 2
12 2
6 3
-3 -4
Step-by-step explanation:
Took the quiz.
In order to solve, set up a proportion: 22/126=x/100. Cross multiply: 2200=126x. Divide by 126 on both sides: 17.46%=x